E-commerce: new forms of work for wealth creation in Zimbabwe - David. I. Fadaraliki , Shepard Chifamb, Walter. T. Mambodza, (International Journal of Scientific Research and Management (IJSRM), 2015)
In the present scenario of the technological world, business is being conducted locally and internationally using electronic means with ease. E-commerce has provided new forms of work in various sectors such as transport, warehousing, insurance, banking, mining, agriculture and communication .However, it is difficult to purchase a product or service online. Ecommerce compromises privacy and consumers tend to lose confidence. This paper will highlight the new forms of work in Ecommerce in Zimbabwe.